The Effect of Sentencing Reform on Crime Rates: Evidence from California's Proposition 47 - Patricio Dominguez-Rivera; Magnus Lofstrom; Steven Raphael (Institute of Labor Economics (IZA), 2019)
We evaluate whether California's state proposition 47 impacted state violent and property crime rates. Passed by the voters in November 2014, the proposition redefined many less serious property and drug offenses that in the past could be charged as either a felony or misdemeanor to straight misdemeanors. The proposition caused a sudden and sizable decline in county jail populations, a moderate decline in the state prison population, a decrease in arrests for property and drug offenses, and a wave of legal petitions filed for retroactive resentencing and reclassification of prior convictions. We make use of multiple strategies to estimate the effect of the proposition, including state-level synthetic cohort analysis, within-state event study estimates based on state-level monthly time series, and a cross-county analysis of changes in county-level crime rates that exploit heterogeneity in the effects of the proposition on local criminal justice practices. We find little evidence of an impact on violent crime rates in the state. Once changes in offense definitions and reporting practices in key agencies are accounted for, violent crime in California is roughly at pre-proposition levels and generally lower than the levels that existed in 2010 prior to a wave major reforms to the state's criminal justice system. While our analysis of violent crime rates yields a few significant point estimates (a decrease in murder for one method and an increase in robbery for another), these findings are highly sensitivity to the method used to generate a counterfactual comparison path. We find more consistent evidence of an impact on property crime, operating primarily through an effect on larceny theft. The estimates are sensitive to the method used to generate the counterfactual, with more than half of the relative increase in property crime (and for some estimates considerably more) driven by a decline in the counterfactual crime rate rather than increases for California for several of the estimators that we employ. Despite this sensitivity, there is evidence from all methods tried that property crime increased with, a ballpark summary of five to seven percent roughly consistent with the totality of our analysis. Similar to violent crime, California property crime rates remain at historically low levels.
Keywords: K40; K42; H11; 330; incarceration; sentencing; crime; jail; prison; Proposition 47